Bibliometric Analysis of Location-Based Marketing - Loso Judijanto (West Science Social and Humanities Studies, 2026)
This study presents a comprehensive bibliometric analysis of location-based marketing (LBM), an evolving field driven by advancements in mobile technology and data-driven marketing strategies. Using data from Scopus, the study examines the intellectual structure, key trends, and emerging themes within LBM research. Findings reveal a central focus on mobile devices, location-based services, and privacy concerns. As mobile technology advances, LBM strategies have become more personalized and targeted, utilizing precise location tracking methods like indoor positioning. Additionally, the study highlights the growing importance of data privacy and ethical marketing practices as consumers become more aware of their digital footprints. The global research network also shows strong collaboration among countries such as the United States, China, and several European nations. The study provides a clear overview of the field's historical development and suggests future research directions.